Interaction of Islamic and Conventional Stock Markets and the Economic Connectivity - MUHARAM, Harjum; WAHYUDI, Sugeng; PANGESTUTI, Irene Rini Demi; NAJMUDIN, NAJMUDIN (Journal of Advanced Research in Law and Economics, 2018)
This paper aims to analyze the dynamic interactions of the Islamic and conventional stock markets and the factors contributing to the interaction. Asymmetric dynamic conditional correlation (ADCC) model, as a recent technique, was applied to identify the interaction and it then acts as a consequence factor in panel data and GARCH(p,q) models regressions. The data were taken from four countries, which consist of developed and emerging markets and have Islamic stocks indices with sample period from January 2000 to December 2016. The results suggest that the stronger dynamic interaction level for all combination pairs was only found among developed markets and in each market. Moreover, the stronger (weaker) interaction level of developed (emerging) stock markets, for both the Islamic and conventional indices, reflects the smaller (greater) inflation rate differential, industrial production growth rate differential, interest rate differential, and exchange rate volatility. In addition, the widespread market crisis affects on interaction level of all stock market pairs.